2011
DOI: 10.1289/ehp.1002873
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Chlorpyrifos Exposure and Effect in Egyptian Cotton Field Workers

Abstract: BackgroundChlorpyrifos (CPF), a widely used organophosphorus pesticide (OP), is metabolized to CPF-oxon, a potent cholinesterase (ChE) inhibitor, and trichloro-2-pyridinol (TCPy). Urinary TCPy is often used as a biomarker for CPF exposure, whereas blood ChE activity is considered an indicator of CPF toxicity. However, whether these biomarkers are dose related has not been studied extensively in populations with repeated daily OP exposures.ObjectiveWe sought to determine the relationship between blood ChE and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
108
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(128 citation statements)
references
References 32 publications
19
108
1
Order By: Relevance
“…This suggestion is supported by the toxicology symptoms ( Table 5) such as loosing appetite and by numerous studies [43] [46]- [47] that reported disturbance of lipid and protein metabolism in animals exposing to organophosphourus insecticides.…”
Section: Demographic and Occupational Parametersmentioning
confidence: 60%
“…This suggestion is supported by the toxicology symptoms ( Table 5) such as loosing appetite and by numerous studies [43] [46]- [47] that reported disturbance of lipid and protein metabolism in animals exposing to organophosphourus insecticides.…”
Section: Demographic and Occupational Parametersmentioning
confidence: 60%
“…With Sri-Lankan and USA farmers, this decline to baseline occurred in approximately 96 h 6,25,26 ). The recent study conducted by Farahat et al 24 indicated that urinary TCP concentration returned to the baseline level in excess of 168 h post application among Egyptian cotton farmers. All of these findings are to be expected, based on the 26.9-h half-life urinary TCP elimination reported by Nolan et al 27 If we assume first order kinetics, then four half-life periods will reduce the maximum value to approximately 6% and 3% of the maximum value, respectively.…”
Section: Post-application Exposure Levels Of Chlorpyrifos (Add a )mentioning
confidence: 96%
“…The possible explanation for this elevated urinary TCP level on day 1 could be the farmers' use of pesticides outside of their main crops. 24 Also, some of farmers were exposed to chlorpyrifos through purchase and preparation of chlorpyrifos for the spraying missions on the next day.…”
Section: Baseline Exposure Levels Of Chlorpyrifos (Add B )mentioning
confidence: 99%
“…BChE in normal group was higher than in exposed group population. Farahat et al (17) organized the studies to seek out the effect of chlorpyrifos -a widely used organophosphates pesticide -on BChE activity, among agriculture worker. It was established that BChE activity decreased gradually by end of the spraying season.…”
Section: Discussionmentioning
confidence: 99%